The contribution of different aerosol types to direct radiative forcing over distinct environments of Pakistan inferred from the AERONET data - Rehana Khan; Kanike Raghavendra Kumar; Tianliang Zhao; Gohar Ali (Environmental Research Letters, 2020)
To quantitatively estimate and analyze the contribution of different aerosol types to radiative forcing, we thoroughly investigated their optical and radiative properties using the Aerosol Robotic Network (AERONET) data (2007–2018) over an urban-industrial (Lahore) and coastal (Karachi) cities located in Pakistan. The contribution of inferred aerosol types following the threshold applied for FMF _500 versus SSA _440 and EANG _440−870 versus AANG _440−870 were found the highest for pure dust (PUD, 31.90%) followed by polluted continental (POC, 24.77%) types of aerosols, with moderate contribution was recorded for polluted dust (POD, 20.92%), organic carbon dominating (OCD, 11.85%), black carbon dominating (BCD, 8.77%) and the lowest for the non-absorbing (NOA, 1.79%) aerosol type. Seasonally, the mean (±SD) aerosol optical thickness at 440 nm (AOT _440 ) was found maximum (0.73 ± 0.36) for PUD type in summer and minimum for BCD (0.25 ± 0.04) during spring at Karachi. However, the mean (±SD) AOT _440 varied from 0.85 ± 0.25 during summer to 0.57 ± 0.30 in winter at Lahore, with the highest contributions for POC (29.91%) and BCD (22.58%) and the lowest for NOA (5.85%) type of aerosols. Further, the intensive optical properties showed significant temporal and spectral changes and the complexity of inferred aerosol types over the study sites. The results are well substantiated with the air mass analysis obtained from the concentration weighted trajectory (CWT) model for different aerosol types. The Santa Barbara DISORT Atmospheric Radiative Transfer (SBDART) model revealed the strong presence of BCD aerosol type led to a surface (BOA) and top of atmosphere (TOA) forcing of −70.12, −99.78 Wm ^−2 and −9.60, −19.74 Wm ^−2 , with an annual heating rate of 2.10 and 2.54 Kday ^−1 , respectively, at Karachi and Lahore sites.